Geometrie da vedere - Ugo Savardi (Rivista di Estetica, 2011)
Spatial perception and spatial representation are not less central to experimental psychology than to visual art. Geometry allows their description and formalization. Therefore, geometrical language can be considered as a kind of generative grammar, which is embedded in the human perceptual experience of space. The paper outlines the suggestion that Euclidean geometry, along with most perspective geometries, even when applied to geometrical problem solving, have phenomenal bases, since they emerge from direct experience of the world, and not necessarily from higher order cognitive processes.